Visualizing and forecasting stocks using Dash - Ooi, Yui Theng (2024)

(untitled)
The need for intuitive and interactive visualization tools is paramount in current stock market environment. Traditional stock market systems provide investors with simple insights and flawless user experiences. This research addresses this gap by proposing a Visualizing and Forecasting Stocks by using Dash that utilizing Power BI. The research identifies the problems in existing systems, such as lack of interactive visualization, inadequate user understanding and unsuitable user interfaces. This research is motivated by the potential for substantial profit in stock forecasting and aims to equip investors with tools to minimize losses and ensure to have a better decision-making. Objectives includes to study the existing stock market system features, developing an interactive forecasting system with intuitive visualization by using dashboards and to evaluate the forecast stock market system dashboard by using usability testing. The methodology for this project is Agile Methodology that separate the projects into planning, analysis, design, development, testing, integration, and maintenance stages. System implementation is relying on Power BI that having a data exploration, visualization, and real time analytics. System evaluation and discussion will include the usability testing questionnaire and basic functionality checks. The results for questionnaire and system testing are overall good and above that shows that the system is in a good direction. In this paper, we aim to provide a stock market system that can visualize and forecast stocks and will focus on incorporating additional stock-related feature in the future enhancements.